Simplify:
$(2x^2 + 3x - 5) (3x^2 - 5x + 4)$

AcademicMathematicsNCERTClass 8

Given:

$(2x^2 + 3x - 5) (3x^2 - 5x + 4)$

To do:

We have to simplify the given expression.

Solution:

$(2x^2 + 3x - 5) (3x^2 - 5x + 4)= 2x^2 (3x^2 - 5x + 4) + 3x (3x^2 - 5x + 4) -5 (3x^2 - 5x + 4)$

$= 2x^2(3x^2) - 2x^2(5x) + 2x^2 (4) + 3x(3x^2)-3x(5x) + 3x(4) - 5 (3x^2) - 5 (-5x) -5(4)$

$= 6x^4-10x^3 + 8x^2 + 9x^3 - 15x^2 + 12x - 15x^2 + 25x-20$

$= 6x^4 - 10x^3 + 9x^3 + 8x^2 - 15x^2 - 15x^2 + 12x + 25x - 20$

$= 6x^4 - x^3 - 22x^2 + 37x - 20$

raja
Updated on 10-Oct-2022 13:19:30

Advertisements